Noxious effects of riot control agents on the ocular surface: Pathogenic mechanisms and management - Quiroga-Garza, Manuel E.; Ruiz-Lozano, Raul E.; Azar, Nadim S.; Mousa, Hazem M.; Komai, Seitaro; Sevilla-Llorca, Jose L.; Perez, Victor L. (Frontiers in Toxicology, 2023)
Riot Control Agents (RCAs) are chemical compounds used by law enforcement agencies to quell violent demonstrations as an alternative to lethal force and as part of police/military training. They are also known as tear gases because of the hallmark ocular irritation and lacrimation they cause. The most common RCAs include oleoresin capsicum (contained in Mace and pepper spray), chlorobenzylidene malononitrile, dibenzoxazepine, and chloroacetophenone (previously the main content of Mace); some of which have been in use for decades. Their immediate incapacitating effects are mediated through polymodal afferent fibers innervating the corneal surface, inducing the release of peptides that cause neurogenic inflammation. Although previously thought to have only transient effects on exposed patients more severe complications such as corneal stromal opacities, corneal neovascularization, neurotrophic keratopathy, conjunctival necrosis, and pseudopterygium can occur. Concerningly, the lack of research and specific therapies restrict the current management to decontamination and symptom-tailored support. This manuscript will provide an overview of the toxic mechanisms of RCAs, their clinical manifestations, and current therapy after exposure to tear gases.